2022
DOI: 10.3389/fcell.2021.784440
|View full text |Cite
|
Sign up to set email alerts
|

Fiber-Like Organization as a Basic Principle for Euchromatin Higher-Order Structure

Abstract: A detailed understanding of the principles of the structural organization of genetic material is of great importance for elucidating the mechanisms of differential regulation of genes in development. Modern ideas about the spatial organization of the genome are based on a microscopic analysis of chromatin structure and molecular data on DNA–DNA contact analysis using Chromatin conformation capture (3C) technology, ranging from the “polymer melt” model to a hierarchical folding concept. Heterogeneity of chromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Still, it is not clear, how chromatin nanostructures form higher levels of chromatin organization. Employing electron tomography, Zakirov et al 54 demonstrated a fiber-like higher-order structure of about 200 nm in diameter (chromonema) of EdU-labeled chromatin (2 h) detected with biotin-streptavidin-mediated nanogold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, it is not clear, how chromatin nanostructures form higher levels of chromatin organization. Employing electron tomography, Zakirov et al 54 demonstrated a fiber-like higher-order structure of about 200 nm in diameter (chromonema) of EdU-labeled chromatin (2 h) detected with biotin-streptavidin-mediated nanogold.…”
Section: Discussionmentioning
confidence: 99%
“…Still, it is not clear, how chromatin nanostructures form higher levels of chromatin organization (Beagrie et al, 2021; Eltsov et al, 2008; Jerkovic and Cavalli, 2021; Minnoye et al, 2021; Zakirov et al, 2022). For an in-depth understanding of these relationships, it is mandatory to produce fully integrated, high-resolution maps, based on the full range of microscopic/biophysical and biochemical approaches (Figure 6c).…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in microscopy have enabled the characterization of euchromatin architecture in vivo, revealing disordered chains of nucleosomes with sporadic clusters ( 28 , 30 , 64 , 65 ). The heterogeneous arrangement of euchromatin differs from the conventional 30-nm chromatin fiber model, which was based on in vitro observations ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies suggest that in vivo chromatin may exhibit a more heterogeneous architecture ( 28 30 ). Euchromatin appears to adopt an open configuration, characterized by disordered nucleosomes separated by variable lengths of linker DNA ( 29 , 30 ).…”
mentioning
confidence: 99%
“…The unit for the resulting metric is arbitrary. Different pairs of parameters are known to lead to similar density maps (Zakirov et al, 2021) . .…”
Section: Ca Segmentation From High Resolution Phase Contrast Microtom...mentioning
confidence: 99%